Pengaruh Modernisasi Terhadap Eksistensi Permainan Tradisional di Gempuran Permainan Modern Bagi Mahasiswa Teknik Lingkungan 2022 - Alifia Putri; Alodisa Putri; Drestanala Hapsari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Modernization is a bridge for humans to start a new era. The digital world which is growing rapidly brings many changes in various aspects and joints of the wider community's life. One of the aspects affected by modernization is the existence of traditional games. Traditional games as we already know are the nation's cultural heritage which has become a culture in Indonesian society. Traditional games are also the nation's cultural wealth. In this research, we aim to review the knowledge of the younger generation, namely UPN "Veteran" East Java Environmental Engineering students Batch 2022 regarding traditional games and their existence in people's daily lives. This study used a qualitative method by interviewing informants to obtain data. The results of this study indicate that the majority of students have started to rarely see traditional games being played in everyday life. Students said that traditional games had not completely disappeared because they were sometimes still played, but only in a few events such as during the independence race.